(untitled) (European Journal of Pure and Applied Mathematics, 2022)
The Abstract Cauchy problem, which is a vector valued differential equation is an important equation in many branches of science. Authors usually study and discuss first and second order abstract Cauchy problem. In this paper, we try to find atomic solutions of the fractional abstract Cauchy problem with order 3Î±, where Î± âˆˆ (0, 1). It turned out that there are so many cases to consider in order to determine atomic solution.